Por uma alfabetização linguística: o professor e o livro didático nos anos iniciais em Penedo/AL - Santos, Déborah dos (2019)
The 2016 Early Literacy National Evaluation report was released at the end of October 2017. The results are disappointing: in Sergipe, only 3.02% of the children who were completing the third year obtained exploitation in level 4 about proficiency in reading, and the state began to occupy the last place in the national classification. In Alagoas, the results were not satisfactory, being that only 4.46% of the students evaluated proved to be suitable for the 4th level (desirable) in reading. Based on these diagnoses, this Msc thesis aimed to analyze those results and point new perspectives about reflection for improvements in the reading and writing teaching in public schools in the 1st year of the city of Penedo, Alagoas, from the one the textbooks analysis adopted by SEMED/Penedo/AL, namely: Sunflower and New sunflower knowledges and doings of the field - Literacy and Literacy - 1st year, Isabella Carpaneda and Angiolina Bragança, the 1st year. This book was chosen for this study due to the large number of public schools that adopt, because, in a amount of 23 schools in the network - between urban and rural areas - 12 show this education feature as the main instrument for literacy. The book analysis had such submissions the theoreticalmethodological assumptions of the Literacy System Scliar, whose teaching and learning methodology stages of reading and writing stands "in which there are more advanced in theory and in the sciences practice dealing with verbal language" (SCLIAR-Cabral, 2013, p. 11). The study reults showed that the methodology adopted in the textbook Sunflower the New Sunflower - literacy and Literacy - 1st year is antagonistic to progress for a literacy scientifically grounded in neuroscience and in recognition in how the reading in the human brain, once the material analyzed presents the letters on the appointment and the sequential alphabet, separating Consonants fromVowels and not according to the articulation complexity of the traits that make up, as showed in the present study. It is believed that in this literacy initial phase it is necessary that the alfabetizador has in mind the criteria for choice of the graphemes according to Scliar-Cabral in its material the Literacy System Scliar (2013) foundation, the study methodological basis, as well as understand the traits simplicity that make up the Graphemes, the individual complexity grafeme articulation, besides the biunivocity the grapheme and the grapheme dependent on linguistic and regional context variable (SCLIAR-Cabral, 2013).